2014
DOI: 10.1038/srep06038
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Electronic Properties of Edge-decorated Graphene Nanoribbons

Abstract: Edge-decorated graphene nanoribbons are investigated with the density functional theory; they reveal three stable geometric structures. The first type is a tubular structure formed by the covalent bonds of decorating boron or nitrogen atoms. The second one consists of curved nanoribbons created by the dipole-dipole interactions between two edges when decorated with Be, Mg, or Al atoms. The final structure is a flat nanoribbon produced due to the repulsive force between two edges; most decorated structures belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…In particular, the edge states in 2D monolayers are found to be extremely important in the design of 2D material-based devices, attributed to their physical, chemical, and electronic properties that are distinct from their intrinsic counterpart 4 13 . Recent experiments and theoretical calculations have revealed that the edge stress can play a dominant role in influencing the intrinsic topology of the monolayer, which can potentially be used to tune the electronic and chemical properties of the edges and their vicinity 14 18 . This has sparked growing interests in understanding the relationship between mechanical, electronic and magnetic properties of stable edges for 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the edge states in 2D monolayers are found to be extremely important in the design of 2D material-based devices, attributed to their physical, chemical, and electronic properties that are distinct from their intrinsic counterpart 4 13 . Recent experiments and theoretical calculations have revealed that the edge stress can play a dominant role in influencing the intrinsic topology of the monolayer, which can potentially be used to tune the electronic and chemical properties of the edges and their vicinity 14 18 . This has sparked growing interests in understanding the relationship between mechanical, electronic and magnetic properties of stable edges for 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, relevant aspects of the emerging materials and technologies can be approached from various standpoints through the formulation of several abstraction levels [6]. Without the ambition to provide their complete and exhaustive list, the most interesting candidates for a replacement of unipolar CMOS technology in the suggested scenario may include silicon nanowires (Si-NWs) [7] [8], carbon nanotubes [9] [10], graphene nanoribbons [11] [12], organic polymers with semiconductor-like properties [13] and presumably even other suitable emerging nanostructures and materials [14], which make it possible to obtain new generation of advanced multi-functional logic elements.…”
Section: Recent Advancements Within the Field Of Digital Design Technmentioning
confidence: 99%
“…Another study [11] suggests the possibility of achieving a half-metallic GNR by doping different species at different edges. Chang et al [12] investigated curved GNRs to simulate unzipping of graphene nanotubes through edge decoration with elements whose atomic number is less than 30. Cervantes-Sodi et al [13] reported detailed studies on the electronic and magnetic properties of edge-decorated GNR with H, N, and O atoms.…”
Section: Introductionmentioning
confidence: 99%